1995
DOI: 10.1034/j.1600-0501.1995.060203.x
|View full text |Cite
|
Sign up to set email alerts
|

Threshold of tactile sensitivity perceived with dental endosseous implants and natural teeth

Abstract: The aim of this study was to determine the threshold of tactile perception of endosseous dental implants and to assess the relative difference of that threshold between implants and teeth. Twenty-two subjects with implants of the ITI Dental Implant System were included in the study. All implants served as abutments for single tooth crowns and had been in function for a minimum of 1 year. A strain gauge glued to the shaft of an amalgam plugger served as a force sensor. It transformed the elastic deformation exe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(101 citation statements)
references
References 0 publications
3
92
1
3
Order By: Relevance
“…However, there is a significant difference in the threshold of tactile sensitivity between teeth replaced by dental implants and natural teeth 23 . It is possible to replace missing teeth with implant retained restorations which have an appearance very similar to natural teeth, but this can be difficult.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a significant difference in the threshold of tactile sensitivity between teeth replaced by dental implants and natural teeth 23 . It is possible to replace missing teeth with implant retained restorations which have an appearance very similar to natural teeth, but this can be difficult.…”
Section: Discussionmentioning
confidence: 99%
“…However, Lan et al [122] suggested that a 0.7-mm occlusal thickness is necessary when applied with an implant. This difference may relate to the loss of periodontal receptors in the implant and the relatively high sensitivity to load compared with natural teeth [123]. As discussed above, rescrewing after a complete restoration in a clinical context is beneficial to reduce screw loosening.…”
Section: Application With Dental Implantsmentioning
confidence: 99%
“…No periodontal ligament receptors are available for tactile function if the tooth is replaced by an endosseous implant 23 . When the threshold of perception of teeth and implants are compared, higher values have been reported for implants.…”
Section: Methodsmentioning
confidence: 99%
“…When the threshold of perception of teeth and implants are compared, higher values have been reported for implants. Hämmerle et al 23 conducted an in vivo study to determine the threshold of tactile perception of (1500-1750Gm). Teeth with a healthy periodontium will show a narrow and sharply delimited zone of terminal TM.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation